2008
DOI: 10.1007/s11207-008-9217-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasmoid Dynamics in Flare Reconnection and the Frequency Drift of the Drifting Pulsating Structure

Abstract: In the paper by Kliem, Karlický, and Benz (Astron. Astrophys. 360, 715, 2000) it was suggested, that plasmoids formed during the bursty regime of solar flare reconnection can be "visualised" in the radio spectra as drifting pulsating structures via accelerated particles trapped inside the plasmoid. In the present paper we investigate this idea in detail. First, simple statistical analysis supporting this hypothesis is presented. Then, by using the 2.5-D MHD (including gravity) model solar flare reconnection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
53
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 16 publications
10
53
0
Order By: Relevance
“…The second feature noticed by Forbes and Priest (1983) has continuously been displayed and duplicated in recent numerical experiments with higher and higher resolutions (Riley et al 2007;Bárta et al 2008Bárta et al , 2010Bárta et al , 2011aBárta et al , 2011bShen et al 2011Shen et al , 2013. These experiments also confirmed that it is inevitable for magnetic islands to form in the CS developed in the coronal environment of high S, and that small islands have a tendency to merge into bigger islands.…”
Section: Cs and Its Internal Fine Structures Observed In Numerical Exsupporting
confidence: 57%
See 2 more Smart Citations
“…The second feature noticed by Forbes and Priest (1983) has continuously been displayed and duplicated in recent numerical experiments with higher and higher resolutions (Riley et al 2007;Bárta et al 2008Bárta et al , 2010Bárta et al , 2011aBárta et al , 2011bShen et al 2011Shen et al , 2013. These experiments also confirmed that it is inevitable for magnetic islands to form in the CS developed in the coronal environment of high S, and that small islands have a tendency to merge into bigger islands.…”
Section: Cs and Its Internal Fine Structures Observed In Numerical Exsupporting
confidence: 57%
“…From an alternative point of view, Bárta et al (2008) performed a simple statistical analysis for the existing observational results, and found the hypothesis of Kliem et al (2000) that internal features could be visualized in the radio spectra supported by observations. By using a 2.5-D MHD model, they simulated reconnection in a Kopp-Pneuman configuration with an inhomogeneous and gravitationally stratified atmosphere, and demonstrated the formation and subsequent ejection of plasmoids inside the CS.…”
Section: Cs and Its Internal Fine Structures Observed In Numerical Exmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there are also the cases when the plasmoids move downwards and the associated DPSs drift to higher frequencies. The plasma density inside the plasmoid differs from that in the surrounding solar atmosphere, therefore this difference needs to be considered in the height estimation of the DPS source in the solar atmosphere from its DPS spectrum (for more details, see Bárta et al 2008a). An example of the DPS observed at the beginning of the May 21, 2002 flare is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The DPSs are usually observed in the frequency range 0.6−2 GHz, which corresponds to the plasma densities in the radio sources n e = 4.4 × 10 9 −4.9 × 10 10 cm −3 . The global drift of DPSs is typically in the range −20−20 MHz s −1 (Bárta et al 2008a).…”
Section: Introductionmentioning
confidence: 99%